2020
DOI: 10.1093/europace/euaa243
|View full text |Cite
|
Sign up to set email alerts
|

In vivoanalysis of the origin and characteristics of gaseous microemboli during catheter-mediated irreversible electroporation

Abstract: Aims  Irreversible electroporation (IRE) ablation is a non-thermal ablation method based on the application of direct current between a multi-electrode catheter and skin electrode. The delivery of current through blood leads to electrolysis. Some studies suggest that gaseous (micro)emboli might be associated with myocardial damage and/or (a)symptomatic cerebral ischaemic events. The aim of this study was to compare the amount of gas generated during IRE ablation and during radiofrequency (RF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…While IRE overcomes many complications associated with thermal ablation techniques, it does pose some similar risks such as thrombosis, haemorrhage and infection, however these are common to all procedures employing similar access techniques [ 50 ]. Specific to IRE there is an associated risk of electrolysis when untuned current is passed through body fluids with dissolved electrolytes, instigating gas formation [ 97 , 98 ]. One study reported that different current polarity may decrease gas bubble formation as a side-effect of IRE, highlighting that a reduced number of gas bubbles are released when using anodal IRE, compared to RF or cathodal IRE [ 98 ].…”
Section: Electroporation As An Ablative Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…While IRE overcomes many complications associated with thermal ablation techniques, it does pose some similar risks such as thrombosis, haemorrhage and infection, however these are common to all procedures employing similar access techniques [ 50 ]. Specific to IRE there is an associated risk of electrolysis when untuned current is passed through body fluids with dissolved electrolytes, instigating gas formation [ 97 , 98 ]. One study reported that different current polarity may decrease gas bubble formation as a side-effect of IRE, highlighting that a reduced number of gas bubbles are released when using anodal IRE, compared to RF or cathodal IRE [ 98 ].…”
Section: Electroporation As An Ablative Approachmentioning
confidence: 99%
“…Specific to IRE there is an associated risk of electrolysis when untuned current is passed through body fluids with dissolved electrolytes, instigating gas formation [ 97 , 98 ]. One study reported that different current polarity may decrease gas bubble formation as a side-effect of IRE, highlighting that a reduced number of gas bubbles are released when using anodal IRE, compared to RF or cathodal IRE [ 98 ]. Gaseous microemboli could result in myocardial damage and in some instances with symptomatic cerebral ischemic events due to the obstruction of capillaries [ 98 ].…”
Section: Electroporation As An Ablative Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…One clinical cerebrovascular event with MRI correlate occurred each in the pilot study with the monopolar single pulse electroporation system (10 patients) as well as in a cohort of 121 patients treated with the Farapulse system 27,38 . This is particularly noteworthy, as the formation of gaseous microemboli is typically detected by intracardiac ultrasound immediately upon electroporation‐based ablation 40,41 . However, although these concerns had already been articulated by the investigators in the respective pilot studies, none of the subsequent clinical studies systematically evaluated cerebral complications by means of cerebral MRI, thus safety data remains incomplete in this respect.…”
Section: Electroporationmentioning
confidence: 99%
“…Evidence that gas bubbles generated from PFA persist and embolize downstream is in the recent study by Groen et al 26 They used a femoral extracorporeal arterial bypass in pigs to measure bubbles originating from 200J multi-unipolar PFA in the left atrium. Their study found that PFA-J o u r n a l P r e -p r o o f generated bubbles (worst case 85 µL volume per PFA application) embolized to the femoral shunt, and their volume was significantly reduced if the anode, not the cathode, is the pole in the atrium.…”
Section: Embolic and Electrochemical Safety Aspectsmentioning
confidence: 99%